Approche méthodologique de quantification de certaines veines émissaires cérébrales - Béatrice Pelissier-Hermitte (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Cerebral blood drainage can be studied on bone remains by measuring the diameters of the canals of the veins which cross the cranium. In this study, we propose a methodology which uses a casting method with a specific material to define the measurements of these vein canals. Our study covers only a part of the original vein canal system, the emissary veins in a sample of modern humans.